Pengetahuan dan Persepsi Remaja Putri terhadap SADARI Sebagai Upaya Deteksi Dini Ca Mammae - Dinanti, Dhea Putri; Asmariyah, Asmariyah; Purnama, Yetti; Yulyani, Linda; Kurnia Pratama, Rini Mustikasari (Lontara Journal of Health Science and Technology, 2026)
Carcinoma Mammae (Ca mammae), commonly known as breast cancer, is a malignancy that occurs in the sacs and ducts that produce milk. One way to detect breast cancer early is through Breast Self-Examination (BSE/SADARI), therefore women need to be aware of the importance of preventing breast cancer by performing BSE. The aim of the research is to determine the relationship between knowledge and perceptions of teenage girls towards BSE behavior as an early detection effort for breast cancer at SMAN 2 Bengkulu City. The research design uses a cross-sectional approach. The number of respondents in this study is 91 respondents and was taken using the stratified random sampling technique. The data collection instrument used was a questionnaire. Data were analyzed using the Spearman's Rho correlation test. The results of this study show that out of 91 respondents, 48 (52.7%) had poor knowledge, 54 (59.4%) had good perception, and 65 (72.5%) had poor behavior. The analysis results with the Spearman Rho test showed a relationship between the level of knowledge and SADARI behavior with a P value of 0.034, while the relationship between perception and SADARI behavior had a P value of 0.000, which means the p value < 0.05. There is a significant relationship between knowledge, perception, and the behavior of female adolescents regarding SADARI at SMAN 2 Kota Bengkulu.